IJPE 2018
DOI: 10.23940/ijpe.18.07.p19.15501559
|View full text |Cite
|
Sign up to set email alerts
|

Predicting and Analysing E-Logistics Demand in Urban and Rural Areas: An Empirical Approach on Historical Data of China

Abstract: With the rapid development of the e-commerce economy in urban and rural areas, China's logistics industry has entered a stage of transformation and upgrade. First, this paper introduces the Supply-Chain Operations Reference-model as a theoretical reference for index selection. Then, after comparing the BP neural network and linear regression analysis, we chose the BP neural network analysis method, which is more stable and accurate in forecasting e-logistics demand scale in urban and rural areas. Finally, acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Huang et al [89] compared a backpropagation (BP) neural network and a linear regression analysis for forecasting of e-logistics demand in urban and rural areas in China using data from 1997 to 2015. By comparing mean absolute error (MAE) and the average relative errors of backpropagation neural network and linear regression, they showed that backpropagation neural networks could reach higher accuracy (reflecting lower differences between predicted and actual data).…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…Huang et al [89] compared a backpropagation (BP) neural network and a linear regression analysis for forecasting of e-logistics demand in urban and rural areas in China using data from 1997 to 2015. By comparing mean absolute error (MAE) and the average relative errors of backpropagation neural network and linear regression, they showed that backpropagation neural networks could reach higher accuracy (reflecting lower differences between predicted and actual data).…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…The ubiquity in internet usage has made positioning and tracking identification and information communication technologies a major part of logistics enterprises [8]. Information infrastructure has become an essential tool in the development process [77,78,79]. For example, in the "Chang-Zhu-Tan" two-oriented social construction area, the use of internet has become a standard infrastructure in its development and urbanization.…”
Section: ) Findingsmentioning
confidence: 99%